CXCL14 Overexpression Attenuates Sepsis-Associated Acute Kidney Injury by Inhibiting Proinflammatory Cytokine Production - Jing Lv; Zhi-Lin Wu; Zheng Gan; Ping Gui; Shang-Long Yao (Mediators of Inflammation)
CXCL14 is a relatively novel chemokine with a wide spectrum of biological activities. The present study was designed to investigate whether CXCL14 overexpression attenuates sepsis-associated acute kidney injury (AKI) in mice. Sepsis model has been established by cecal ligation and puncture (CLP). CLP induced AKI in mice as assessed by increased renal neutrophil gelatinase-associated lipocalin (NGAL) expression and serum creatinine levels. We found that renal CXCL14 expression in the kidney was significantly decreased at 12 hours after CLP. Correlation analysis demonstrated a negative association between renal CXCL14 expression and AKI markers including serum creatinine and renal NGAL. Moreover, CXCL14 overexpression reduced cytokine (TNF-α, IL-6, and IL-1β) production and NGAL expression in the kidney and decreased serum creatinine levels. In vivo and in vitro experiments found that CXCL14 overexpression inhibited M1 macrophage polarization but increased M2 polarization. Together, these results suggest that CXCL14 overexpression attenuates sepsis-associated AKI probably through the downregulation of macrophages-derived cytokine production. However, further studies are required to elucidate the underlying mechanism.